Hippocampal volume predicts fluid intelligence in musically trained people. Issue 7 (29th April 2013) - Oechslin, Mathias S.; Descloux, Céline; Croquelois, Alexandre; Chanal, Julien; Van De, Dimitri; Lazeyras, François; James, Clara E.
ABSTRACT Recently, age‐related hippocampal (HP) volume loss could be associated with a decrease in general fluid intelligence (gF). In the present study we investigated whether and how extensive musical training modulates human HP volume and gF performance. Previously, some studies demonstrated positive effects of musical training on higher cognitive functions such as learning and memory, associated with neural adaptations beyond the auditory domain. In order to detect possible associations between musical training and gF, we bilaterally segmented the HP formation and assessed the individual gF performance of people with different levels of musical expertise. Multiple regression analyses revealed that HP volume predicts gF in musicians but not in nonmusicians; in particular, bilaterally enhanced HP volume is associated with increased gF exclusively in musically trained people (amateurs and experts). This result suggests that musical training facilitates the recruitment of cognitive resources, which are essential for gF and linked to HP functioning. Musical training, even at a moderate level of intensity, can thus be considered as a potential strategy to decelerate age‐related effects of cognitive decline. © 2013 Wiley Periodicals, Inc.